Bmal1 knockdown in the left stellate ganglion inhibits neural activity and prevents ventricular arrhythmias after myocardial ischemia - Yu, Zhongyang; Liu, Zhihao; Jiao, Liying; Zhang, Song; Nie, Liqing; Wang, Yueyi; Zhou, Liping; Wang, Yuhong; Liu, Zhihao; Liu, Zihan; Xu, Xiao; Li, Zeyan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The neural activity of the left stellate ganglion (LSG) is closely related to the occurrence of ventricular arrythmias (VAs). Bmal1 modulates genes associated with neural activity in the central nervous system. However, few studies studied the role of Bmal1 in the LSG and the subsequent effect in heart. Therefore, we aimed to investigate the influence of Bmal1 knockdown in the LSG on its neural activity and cardiac electrophysiology and to explore the mechanisms. Methods We used adeno-associated virus (AAV) to knock down Bmal1 in the LSG. Male beagles were randomized into the Bmal1 knockdown group and the control group. 4 weeks later injection, LSG function, neural activity, left ventricular effective refractory period (ERP) and action potential duration (APD) were measured. 1h of electrocardiography was recorded for VAs analysis after myocardial ischemia. NGF and c-fos in the LSG were quantified by immunofluorescence. Transcriptomic analysis was performed to assess the gene expression in the LSG. Results Bmal1 was sufficiently knocked down by AAV. Compared with the control group, HRV in the knockdown group was altered. Bmal1 knockdown inhibited neural activity and function of LSG. It also prolonged ERP as well as APD90. Ischemia-induced VAs were significantly reduced. NGF and c-fos in the LSG were reduced. Bmal1 knockdown led to the expression changes of genes associated with neural activity in the LSG. Conclusion Bmal1 knockdown in the LSG suppresses the neural activity and prevents ventricular arrhythmias after myocardial ischemia.